2021
DOI: 10.1093/nar/gkab157
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA editing by intracellular acidification

Abstract: The hydrolytic deamination of adenosine-to-inosine (A-to-I) by RNA editing is a widespread post-transcriptional modification catalyzed by the adenosine deaminase acting on RNA (ADAR) family of proteins. ADAR-mediated RNA editing modulates cellular pathways involved in innate immunity, RNA splicing, RNA interference, and protein recoding, and has been investigated as a strategy for therapeutic intervention of genetic disorders. Despite advances in basic and translational research, the mechanisms regulating RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…20,23 Indeed, recently described pH effects on the deamination rates for wild-type and E488Q mutant ADAR2 support this hypothesis. 24 These observations inspired us to test orphan base analogs capable of hydrogen bonding with the wild-type E488 residue in a protonation-independent manner. By stabilizing the same contact made by the mutant enzyme, this may allow wild-type ADAR2 to elicit a similar hyperactive effect.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,23 Indeed, recently described pH effects on the deamination rates for wild-type and E488Q mutant ADAR2 support this hypothesis. 24 These observations inspired us to test orphan base analogs capable of hydrogen bonding with the wild-type E488 residue in a protonation-independent manner. By stabilizing the same contact made by the mutant enzyme, this may allow wild-type ADAR2 to elicit a similar hyperactive effect.…”
Section: ■ Resultsmentioning
confidence: 99%
“…MBP-tagged human ADAR1 p110 wild-type (hADAR1 p110 WT) was expressed as previously described. 24 Purification of hADAR1 p110 was carried out by lysing cells in buffer containing 50 mM Tris-HCl, pH 8.0, 5% glycerol, 5 mM BME, 1000 mM KCl, 50 μM ZnCl 2 , and 0.05% NP-40 using a microfluidizer. Cell lysate was clarified by centrifugation (39 000 × g for 50 min).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…On the basis of increased expression of ISGs such as Ifit1 that are induced by IRF3 and IRF7, we propose that non-hematopoietic cell types as well as neutrophils initiate the IFN response in Adar1 mZα/mZα lungs. Interestingly, a recent study showed that RNA editing increases upon intracellular acidification ( Malik et al., 2021 ). Neutrophils produce different types of acids ( Ulfig and Leichert, 2021 ), which may explain the induction of type I IFN responses in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors could show that intracellular acidification modulates ADAR catalytic activity directly. This is possible due to enhanced flipping out of the adenosine to be edited and additionally an increased deamination rate at a more acidic pH [ 67 ] ( Figure 2 ).…”
Section: Regulation Of Adar Activitymentioning
confidence: 99%